Targeting KRAS mutations in pancreatic cancer: opportunities for future strategies - Linehan, Anna; O’Reilly, Mary; McDermott, Ray; O’Kane, Grainne M. (Frontiers in Medicine, 2024)
Targeting the RAS pathway remains the holy grail of precision oncology. In the case of pancreatic ductal adenocarcinomas (PDAC), 90–92% harbor mutations in the oncogene KRAS, triggering canonical MAPK signaling. The smooth structure of the altered KRAS protein without a binding pocket and its affinity for GTP have, in the past, hampered drug development. The emergence of KRASG12C covalent inhibitors has provided renewed enthusiasm for targeting KRAS. The numerous pathways implicated in RAS activation do, however, lead to the development of early resistance. In addition, the dense stromal niche and immunosuppressive microenvironment dictated by oncogenic KRAS can influence treatment responses, highlighting the need for a combination-based approach. Given that mutations in KRAS occur early in PDAC tumorigenesis, an understanding of its pleiotropic effects is key to progress in this disease. Herein, we review current perspectives on targeting KRAS with a focus on PDAC.